2021
DOI: 10.3389/fpsyg.2021.685180
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown Effects on Healthy Cognitive Aging During the COVID-19 Pandemic: A Longitudinal Study

Abstract: The COVID-19 pandemic is a health issue leading older adults to an increased vulnerability to unfavorable outcomes. Indeed, the presence of physical frailty has recently led to higher mortality due to SARS-CoV-2 infection. However, no longitudinal studies have investigated the role of neuropsychogeriatric factors associated with lockdown fatigue in healthy cognitive aging. Eighty-one healthy older adults were evaluated for their neuropsychological characteristics, including physical frailty, before the pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 52 publications
3
36
1
Order By: Relevance
“…Indeed, during a difficult period, such as the COVID-19 pandemic, social distancing and isolation might exacerbate sleep problems and psychological distress already present in the older population, leading to greater negative health status outcomes [50]. Moreover, cognitive, psychological, and functional aspects in older adults in healthy aging may have a critical role in both fatigue due to home confinement restrictive measures [52] and the perceived threat of SARS-CoV-2's risk of contagion [54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, during a difficult period, such as the COVID-19 pandemic, social distancing and isolation might exacerbate sleep problems and psychological distress already present in the older population, leading to greater negative health status outcomes [50]. Moreover, cognitive, psychological, and functional aspects in older adults in healthy aging may have a critical role in both fatigue due to home confinement restrictive measures [52] and the perceived threat of SARS-CoV-2's risk of contagion [54].…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, some studies showed associations between sleep problems and mood changes; other studies considered the impact of individual aspects, lifestyle, and attitudes adopted by older adults during the COVID-19 lockdown; finally, others found no significant differences in sleep patterns comparing before with during the pandemic period. In our recent study [52], which aimed to analyze the influence of cognitive, psychological, and functional factors on the lockdown fatigue, we also asked a group of healthy aging subjects if they had experienced any lifestyle changes, such as in sleep quality, during the COVID-19 home confinement. Consistent with the evidence in the literature, we observed heterogeneous results (i.e., improvement, similarity, and worsening, in 12, 56, and 32% of the sample, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of COVID-19 containment measures, older adults may experience physical and other mental health problems [5], such as depressive mood and anxiety-related fear of contagion [6]. In line with these aspects, a recent study [7] highlighted how both cognitive and physical issues related to the COVID-19 pandemic may play a key role in the novel "lockdown fatigue". In particular, the authors found that pandemic fatigue was associated with decreased processing and walking speed and with mood changes in terms of depression.…”
Section: Introductionmentioning
confidence: 99%